2022
DOI: 10.3389/fped.2022.857106
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Cardiac Output Monitoring and Assessment of Fluid Responsiveness in Children With Shock in the Emergency Department

Abstract: IntroductionThe assessment of fluid responsiveness is important in the management of shock but conventional methods of assessing fluid responsiveness are often inaccurate. Our study aims to evaluate changes in objective hemodynamic parameters as measured using electrical cardiometry (ICON® monitor) following the fluid bolus in children presenting with shock and to evaluate whether any specific hemodynamic parameter can best predict fluid responsiveness among children with shock.Materials and MethodsWe conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…EC has demonstrated both accuracy and efficiency in hemodynamic monitoring in critically ill children; however, very few have investigated FR. 33 65 66 67 Three studies verified the utility of NICOM-derived SVV in predicting FR in the postoperative period. 26 63 68 Interestingly, patients were mechanically ventilated in two of these studies, and spontaneously breathing in one, thus supporting the reliability of NICOM in both clinical situations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…EC has demonstrated both accuracy and efficiency in hemodynamic monitoring in critically ill children; however, very few have investigated FR. 33 65 66 67 Three studies verified the utility of NICOM-derived SVV in predicting FR in the postoperative period. 26 63 68 Interestingly, patients were mechanically ventilated in two of these studies, and spontaneously breathing in one, thus supporting the reliability of NICOM in both clinical situations.…”
Section: Discussionmentioning
confidence: 87%
“…Awadhare et al investigated a variety of parameters after fluid bolus, including CI, SI, and ∆ICON. 67 While all were good indicators of FR, ∆ICON of 15% demonstrated by NICOM after fluid bolus was most predictive. In the final study, after investigation of PLR in conjunction with CI, Lu et al concluded that at least a 7.5% increase in CI was only predictive in children over 5 years old with 100% sensitivity, which raises uncertainty regarding age limitations for NICOM use.…”
Section: Discussionmentioning
confidence: 92%
“…This current endeavor follows a recent study from our institution by Awadhare et al that evaluated a fluid bolus challenge in tandem with the same ICON® monitor. 16 Aside from identifying significant changes in TFC, STR, MAP, and SVR, our prior study concluded that a 15% change in the ICON had strong predictive value in fluid responsiveness. 16 The differing findings in the current study highlight potential incongruences between observed volume expansion provided by the PLR maneuver compared with a physical fluid bolus.…”
Section: Discussionmentioning
confidence: 95%
“…This determination is known as "fluid responsiveness" and is broadly defined as a 10 to 15% increase in either stroke volume (SV) or cardiac output (CO) following crystalloid fluid bolus. [14][15][16] Passive leg raise (PLR) is a bedside maneuver in which the patient's lower extremities are raised to 45 degrees, to simulate administration of an "auto-bolus." Essentially, this maneuver is thought to facilitate rapid venous return from the lower extremities and augment preload, 17 manifested in both subjective and objective clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation